Complete Chloroplast Genome Analysis of Two Important Medicinal Alpinia Species: Alpinia galanga and Alpinia kwangsiensis - Zhang, Yue; Song, Mei-Fang; Li, Yao; Sun, Hui-Fang; Tang, Dei-Ying; Xu, An-Shun; Yin, Cui-Yun; Zhang, Zhong-Lian; Zhang, Li-Xia (Frontiers in Plant Science, 2021)
Most Alpinia species are valued as foods, ornamental plants, or plants with medicinal properties. However, morphological characteristics and commonly used DNA barcode fragments are not sufficient for accurately identifying Alpinia species. Difficulties in species identification have led to confusion in the sale and use of Alpinia for medicinal use. To mine resources and improve the molecular methods for distinguishing among Alpinia species, we report the complete chloroplast (CP) genomes of Alpinia galanga and Alpinia kwangsiensis species, obtained via high-throughput Illumina sequencing. The CP genomes of A. galanga and A. kwangsiensis exhibited a typical circular tetramerous structure, including a large single-copy region (87,565 bp and 87,732 bp, respectively), a small single-copy region (17,909 bp and 15,181 bp, respectively), and a pair of inverted repeats (27,313 bp and 29,705 bp, respectively). The guanine–cytosine content of the CP genomes is 36.26% and 36.15%, respectively. Furthermore, each CP genome contained 133 genes, including 87 protein-coding genes, 38 distinct tRNA genes, and 8 distinct rRNA genes. We identified 110 and 125 simple sequence repeats in the CP genomes of A. galanga and A. kwangsiensis, respectively. We then combined these data with publicly available CP genome data from four other Alpinia species (A. hainanensis, A. oxyphylla, A. pumila, and A. zerumbet) and analyzed their sequence characteristics. Nucleotide diversity was analyzed based on the alignment of the complete CP genome sequences, and five candidate highly variable site markers (trnS-trnG, trnC-petN, rpl32-trnL, psaC-ndhE, and ndhC-trnV) were found. Twenty-eight complete CP genome sequences belonging to Alpinieae species were used to construct phylogenetic trees. The results fully demonstrated the phylogenetic relationship among the genera of the Alpinieae, and further proved that Alpinia is a non-monophyletic group. The complete CP genomes of the two medicinal Alpinia species provides lays the foundation for the use of CP genomes in species identification and phylogenetic analyses of Alpinia species.